Mastering elasticsearch : further your knowledge of the elasticsearch server by learning more about its internals, querying, and data handling /: further your knowledge of the elasticsearch server by learning more about its internals, querying, and data handling. (2015) - Kuc, Rafał; Rogozinski, Marek
No abstract available